2018
DOI: 10.1371/journal.pone.0189298
|View full text |Cite
|
Sign up to set email alerts
|

Consumer physical activity tracking device ownership and use among a population-based sample of adults

Abstract: Consumer physical activity tracking devices (PATs) have gained popularity to support individuals to be more active and less sedentary throughout the day. Wearable PATs provide real-time feedback of various fitness-related metrics such as tracking steps, sedentary time, and distance walked. The purpose of this study was to examine the prevalence and correlates of PAT ownership and use among a population-based sample of adults. A representative sample of adults ≥18 years (N = 1,215) from Alberta, Canada were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 39 publications
6
44
0
Order By: Relevance
“…ATD users wore it for an average of 23 days in the month preceding the survey. 29 The participants who owned an ATD, but who no longer used it, reported they wore the ATD for ∼8 months before they stopped wearing it altogether. Another report from a national cross-sectional survey found that 37% used an ATD for 1 month, 35% for 1–6 months, and 27% for more than 1 month.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATD users wore it for an average of 23 days in the month preceding the survey. 29 The participants who owned an ATD, but who no longer used it, reported they wore the ATD for ∼8 months before they stopped wearing it altogether. Another report from a national cross-sectional survey found that 37% used an ATD for 1 month, 35% for 1–6 months, and 27% for more than 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings that participants did not engage in the community forums are similar to those of Macridis et al who reported that 51% of their participants did not find connecting with friends/family for step challenges useful. 29 To protect participant confidentiality, no identifying information was posted to the community forums. Lack of identity may have diminished the attractiveness of connecting with other pregnant women in this manner.…”
Section: Discussionmentioning
confidence: 99%
“…No longer an exclusive domain of fitness and quantified-self enthusiasts, wearable health and activity monitors are breaking into the mainstream. For example, a recent survey conducted among the adult population of Alberta, Canada [3] found that one-fifth of the sample own and use a wearable physical activity tracker. The companies that design and manufacture these devices cater for a wide range of market segments, and an entry-level product can now be bought for well under 100 USD.…”
Section: Introductionmentioning
confidence: 99%
“…Smartwatches and fitness trackers are the most popular wearable devices, with activity tracking being one of its main uses. The sharp increase in sales makes it difficult to assess the prevalence of the devices but a recent estimate puts at 20% the number of users in Canada [1], while a survey conducted in 2015 among US adults estimated that 12.5% used fitness trackers [2].The proliferation of these devices has promoted their use in healthcare research [3], particularly in studies aimed at measuring physical activity, sleep and heart rate [4]. For instance, the analysis of more than 15,000 individuals using wearable devices found that these activity trackers provide useful information to identify individuals at risk of poor sleep [5].…”
Section: Introductionmentioning
confidence: 99%